2016
DOI: 10.1136/jmedgenet-2015-103695
|View full text |Cite
|
Sign up to set email alerts
|

NovelLMNAmutations cause an aggressive atypical neonatal progeria without progerin accumulation

Abstract: Our results demonstrate the causal role of p.E55K and p.E55G lamin A mutations in a disorder which manifests novel phenotypic features of the progeria spectrum characterised by neonatal presentation and aggressive clinical evolution, despite being caused by lamin A/C missense mutations with effective prelamin A processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Mandibulo-acral dysplasia, due to mutations in LMNA or ZMPSTE24 , was identified as the first laminopathy associating premature ageing and lipodystrophic features [ 63 , 64 ]. This phenotypic combination was further observed with other LMNA mutations in typical Hutchinson-Gilford progeria [ 66 , 67 ] or in atypical progeroid syndromes [ 65 , 68 , 69 ].…”
Section: Defects In Adipocyte Differentiation In Lmna supporting
confidence: 56%
“…Mandibulo-acral dysplasia, due to mutations in LMNA or ZMPSTE24 , was identified as the first laminopathy associating premature ageing and lipodystrophic features [ 63 , 64 ]. This phenotypic combination was further observed with other LMNA mutations in typical Hutchinson-Gilford progeria [ 66 , 67 ] or in atypical progeroid syndromes [ 65 , 68 , 69 ].…”
Section: Defects In Adipocyte Differentiation In Lmna supporting
confidence: 56%
“…Segmental progeroid syndromes, defined as syndromes with signs of premature aging affecting more than one tissue or organ (Martin 1978), are highly heterogenous genetic disorders. Studies utilizing next-generation sequencing (NGS) approaches have revealed several novel progeroid genes in recent years (Ehmke et al 2017;Jay et al 2016;Lessel et al 2014bLessel et al , 2017bLessel et al , 2018Marbach et al 2019;Paolacci et al 2018;Puente et al 2011;Schrauwen et al 2015;Wambach et al 2018), and broadened the spectrum of phenotypes of many known progeroid conditions and the number of associated genetic causes (Lessel et al 2014a(Lessel et al , 2015Rodriguez-Garcia et al 2018;Soria-Valles et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an atypical aggressive neonatal form of HGPS without progerin accumulation has been reported. The molecular exploration found an association of two de novo heterozygous point mutations in LMNA : c.163G > A, p.E55K and c.164A > G, p.E55G [ 58 ].…”
Section: Diseases Caused By Mutations Affecting Proteins Of the Nuclementioning
confidence: 99%